2017
DOI: 10.1021/acsomega.7b00170
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Activation in Chiral Brønsted Acid-Catalyzed Intramolecular α-Amidoalkylation Reactions for the Synthesis of Fused Isoquinolines

Abstract: An organolithium addition–intramolecular α-amidoalkylation sequence on N -phenethylimides has been developed for the synthesis of fused tetrahydroisoquinoline systems using 1,1′-bi-2-naphthol (binol)-derived Brønsted acids. This transformation is the first in which activated benzene derivatives are used as internal nucleophiles, instead of electron-rich heteroaromatics, generating a quaternary stereocenter. Phenolic substitution on the aromatic ring of the phenethylamino moiety and the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 89 publications
(76 reference statements)
0
11
0
Order By: Relevance
“…The absence of strong hydrogen bonding donors results in the participation of only one imide carbonyl in hydrogen bonding. The selective activation of one imide carbonyl group of the N -phenethylimides by Brønsted acids, such as BBr 3 [ 34 ], TfOH [ 35 ] or organometallics [ 36 ], leads to regioselective intramolecular cyclization to deliver tetrahydroisoquinoline derivatives [ 37 , 38 ]. This selective regiochemical polarization could be involved in the mode of action of compound 1 as an AChEI, as previously proposed [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…The absence of strong hydrogen bonding donors results in the participation of only one imide carbonyl in hydrogen bonding. The selective activation of one imide carbonyl group of the N -phenethylimides by Brønsted acids, such as BBr 3 [ 34 ], TfOH [ 35 ] or organometallics [ 36 ], leads to regioselective intramolecular cyclization to deliver tetrahydroisoquinoline derivatives [ 37 , 38 ]. This selective regiochemical polarization could be involved in the mode of action of compound 1 as an AChEI, as previously proposed [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…The present protocol rely on organolithium addition-intramolecular α-amidoalkylation pattern on N-phenethylimides 487 (Scheme 295). [293] Chen et al have demonstrated a protecting-groupfree intramolecular thermal cyclization of methyl 2-[(diphenylmethylidene)amino]-acetates 490 to access 1-phenylisoquinolin-4-ols 491. It was found that substitutions on Schiff's base affecting the yields of the reaction products (Scheme 296).…”
Section: Non-metal Catalyzed Isoquinoline Synthesis and Other Methodsmentioning
confidence: 99%
“…Since the elegantc ontribution of chiral phosphoric acids as Brønsteda cid catalysts independently discovered by the groups of Akiyama [39] and Te rada [40] in 2004, continuous attentions have been attracted by chiral Brønsted acid catalysis and these catalysts have been regarded as powerful organocatalysts for asymmetrics ynthesis. [41] The different kinds of chiral Brønsteda cids have been prepared and exhibited to enable numberso fe nantioselective transformations.…”
Section: Ferrocene-based Brønsted Acid Organocatalystsmentioning
confidence: 99%